A Call to Reform Secondary Schools in Kenya - Amukowa, Wycliffe (American International Journal of Contemporary Research, 2013)
This paper is a thesis to the effect that secondary schools in Kenya frustrate learners thereby undermining the achievement of Kenya’s goals of education. In particular the paper discusses how secondary schools in Kenya are leading to the erosion of national cohesion, disfiguration of the Kenya youth and the growth of moral decadence among other social and personal ills. In this regard, the paper calls for an end to the current categorization of secondary schools into national, provincial and district/county levels.
Keywords: Education; Kenya; Schools; Reforms